(untitled) (Cadernos de Sociomuseologia, 2019)
This work, which is part of the Museology studies, aims at a call for attention through this important disciplinary area, for the preservation of the environment as a heritage. We refer to the relationship between Museums and the environment and some international documents that support the introduction of environmental concerns and their sustainability in museology. We will make reference to some types of Museums with respect to their architecture and type of construction and, we point out technical solutions available in the market for the energy sources that we consider more appropriate, regarding the individual or collective insertion of equipment for the capture and production of renewable and clean energies in these cultural facilities. Keywords: Museums, Museology, Sociomuseology, Renewable Energies, Environmental Sustainability.